Shapley Value Allocation Approach to Assess Conflicts Over Logone River Basin - Ernest, Maya; Ibrahim, Ngouhouo (Research Aspects in Arts and Social Studies Vol. 7, 2023)
The objective of this paper is to apply game theory tools to resolve conflicts over the water allocation problem in the logone river basin. Natural resources management is the manipulation of resource-producing natural systems to optimize their long-term productivity for both human use and biological production. The use of water in the Logone Basin has been a major source of contention between users such as farmers and fishermen. In this paper, we look at how cooperative game theory can help us understand the importance of coordination. A positive mathematical programming is used to determine the net agricultural benefit of the players in the water management competition. The Shapley value method is used for the second time to find the appropriate equilibrium that satisfies all users. This method was applied to the real-world case of the Logone River, which is one of the rivers suffering from water scarcity in the Lac Chad basin. The study also demonstrated that cooperative game theory can be applied to resolve water conflicts and the authority can then implement institutions that urge to coordination.